ASSESSING THE PHYSICAL PROPERTIES OF SOIL ON FREQUENTLY PLANTED LAND WITH SHALLOTS AT GUNTARANO VILLAGE, DONGGALA REGENCY, CENTRAL SULAWESI - Anthon Monde; Bunga Elim Somba; Abner Lionel (AGROLAND The Agricultural Sciences Journal (e-Journal), 2023)
The red onion of the Palu Valley variety is a type of shallot that grows well in the Palu valley and its surroundings. It has a distinctive taste when fried, so it is one of the souvenirs from the city of Palu. This study aimed at examining the soil’s physical properties on land often planted with shallots. This research was conducted in Guntarano Village, Donggala Regency. Soil samples were analysed at the Laboratory of Soil Science, Faculty of Agriculture, University of Tadulako. The research was carried out from June to November 2022. The method used was a survey method and the research location was determined deliberately (purposive sampling). The soil samples were taken on shallot farming land at flat and back of the slope. Depending on the area of the land, there were five composite samples where each composite sampling representing from 5-10 points of observation. The results of analystzing the physical properties of the soil showed that the shallot fields had a crumb to lumpy soil structure; medium to heavy bulk density; soil organic matter varied from medium to high; and water conten at field capacity range from 16.12% to 22.85%. The soil in the shallot farming area has begun to show poor soil quality due to high soil porosity (66,09 %) and high soil permeability (13,10 cm/hour).